Fungal functional metabolism succession contributes to product efficiency during co-composting of domestic garbage and cow manure - Cece Qiao; Libin Bao; Qinjuan Zhang; Xie Yiqin; Lantian Ren; Wenge Wu; Wenge Wu; Jianfei Wang (Frontiers in Sustainable Food Systems)
Improving composting efficiency by adding domestic garbage and analyzing the associated microbial mechanisms constitute the foundation for promoting the utilization of agricultural waste. The present study investigated composting efficiency and the underlying fungal mechanisms associated with different domestic garbage amendments using industrial-scale aerobic composting. The results indicated that the amendment of domestic garbage significantly improved composting efficiency, as evidenced by elevated temperatures, higher germination index (GI) values, and increased cellulose and hemicellulose transformation. Fungal community composition was found to differ according to both the composting stage (PERMANOVA, F = 14.03, p < 0.01) and treatment (PERMANOVA, F = 5.92, p < 0.01). The functional profiles of the fungal community, derived from the bioinformatic tool FUNGuild, showed that the activities of typical functional guilds—symbiotrophic (r = −0.913) and pathogenic (r = −0.926) fungi—were significantly negatively correlated with compost maturity, while saprotrophic fungi (r = 0.947) were positively correlated with composting maturity. Therefore, high-efficiency composting could be considered a process characterized by the gradual decline of symbiotrophic and pathogenic fungi, accompanied by their replacement with saprotrophic fungi. These putative functional guilds were influenced by key environmental factors, such as the C/N ratio, TOC, and cellulose content, thereby playing a significant role in enhancing composting efficiency. The greenhouse pot experiments with maize seedlings exhibited that the composting end product derived from domestic garbage amendments significantly promoted growth. Taken together, this study provides deeper insight into how functional ecological groups within the fungal community contribute to enhanced composting performance.